2008
DOI: 10.1007/s10495-008-0237-2
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of JNK regulation in oxidative stress-mediated murine liver injury by microcystin-LR

Abstract: Microcystin-LR (MC-LR) produced by cyanobacteria in diverse water systems is a potent specific hepatotoxin and has been documented to induce various liver diseases via oxidative stress. However, the underlying mechanisms are largely unknown. In the current study, we investigated the molecular events involved in the oxidative liver injury by MC-LR. Our results demonstrated that MC-LR induced liver injury in mice through a series of steps that began with the production of reactive oxygen species (ROS), which sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 50 publications
2
49
0
Order By: Relevance
“…Zhang et al [34] reported endoplasmic reticulum (ER) stress as an event that occurs downstream of oxidative stress and found that MCs exposure may induce testis apoptosis involving both the mitochondrial and ER pathways. It was also confirmed that MC-LR-induced oxidative stress may stimulate sustained activation of JNK, which in turn induced apoptosis via AP-1 and Bid, two important substrates downstream of JNK [124]. Moreover, MCs could lead to cytoskeleton disruption and the cytoskeleton may also play a key role in regulating apoptosis and necrosis in reproductive system (Fig.…”
Section: Apoptosis/necrosismentioning
confidence: 68%
“…Zhang et al [34] reported endoplasmic reticulum (ER) stress as an event that occurs downstream of oxidative stress and found that MCs exposure may induce testis apoptosis involving both the mitochondrial and ER pathways. It was also confirmed that MC-LR-induced oxidative stress may stimulate sustained activation of JNK, which in turn induced apoptosis via AP-1 and Bid, two important substrates downstream of JNK [124]. Moreover, MCs could lead to cytoskeleton disruption and the cytoskeleton may also play a key role in regulating apoptosis and necrosis in reproductive system (Fig.…”
Section: Apoptosis/necrosismentioning
confidence: 68%
“…Previous studies have indicated that MCs can exert harmful toxicity on mammals (Clark et al 2009), birds (Peckova et al 2009) and aquatic animals such as cladocerans and fish (Malbrouck and Kestemont 2006;Okumura et al 2007). Wei et al (2008b) revealed that MCs exposure induces adaptive responses to enhance the antioxidant enzymatic activities. MCs also constitute a carcinogenic risk to people via drinking water and food chains (Ueno et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…MCs also constitute a carcinogenic risk to people via drinking water and food chains (Ueno et al 1996). Currently, most attention is focused on the carcinogenic mechanism of MCs (Wei et al 2008b;Hernandez et al 2009), but limited information is available about its effects on cellular infiltration and migration, and in turn on tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…The liver has been described as the most important organ involved in the regulation of redox metabolism (Wei et al 2008), and it is the target organ of many pollutants (Albina et al 2010;Ding and Ong 2003). Consequently, its oxidative status may be affected by such pollutants.…”
Section: Discussionmentioning
confidence: 99%